2012
DOI: 10.1002/bit.24625
|View full text |Cite
|
Sign up to set email alerts
|

Methanol‐driven enhanced biological phosphorus removal with a syntrophic consortium

Abstract: This is the accepted version of the following article: Tayà Cristellys, Carlota et al. "Methanol-driven enhanced biological phosphorus removal with a syntrophic consortium" in Biotechnology and Bioengineering, Vol. 110, Issue 2 (February 2013), p.391 -400, which has been published in final form at 10.1002/bit.24625. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving. 2 ABSTRACTThe presence of suitable carbon sources for enhanced biological phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Methanol could be a good example of such fermentable components since it is present in crude glycerol in non-negligible concentrations (i.e. it is used during biodiesel production) and it could be fermented to acetic acid under specific conditions (Tayà et al, 2013). According to Pijuan et al (2005), PHB is mostly produced when acetic acid is used as carbon source.…”
Section: Sbr Operation With Crude Glycerolmentioning
confidence: 99%
See 3 more Smart Citations
“…Methanol could be a good example of such fermentable components since it is present in crude glycerol in non-negligible concentrations (i.e. it is used during biodiesel production) and it could be fermented to acetic acid under specific conditions (Tayà et al, 2013). According to Pijuan et al (2005), PHB is mostly produced when acetic acid is used as carbon source.…”
Section: Sbr Operation With Crude Glycerolmentioning
confidence: 99%
“…Methanol is the most common external carbon source used for denitrification, but its utilization for EBPR has conducted to numerous failures (Puig et al, 2008;Randall et al, 1997b) before being successfully reported in a recent work (Tayà et al, 2013). PAO-enriched biomass in a conventional anaerobic-aerobic sequencing batch reactor (SBR) was unable to survive using methanol as sole carbon source when a direct replacement for propionic acid in the work of Tayà et al (2013).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several external carbon sources have been studied to balance the COD deficiency in wastewaters (Gerber et al, 1986;Jones, et al, 1987;Winter, 1989;Appeldoorm, et al, 1992;Isaacs et al, 1994;Hallin. et al, 1996;Guerrero et al, 2012;Tayà et al, 2012). Among those, acetic and propionic acids were suggested as the most effective carbon sources for improving BNR.…”
Section: Introductionmentioning
confidence: 99%